MODEL PROFIT ECONOMIC ON FEMALE WORKERS IN INDONESIA - Hakim, Lukmanul; Ma'ruf, M. Hasan; Pratama, Yan Aditiya; Herwanto, Riko; Suranti, Yuli (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study was to analyze the effect of service quality, professionalism of BKPSDM employees on the level of satisfaction of married female civil servants and female civil servants. The method of the study used associative using multiple linear regression data analysis techniques. This study used accidental sampling technique by using a sample of 100 respondents. The results of the study partially and simultaneously showed that the service quality and professionalism of BKPSDM employees affected the level of satisfaction of married female civil servants by 46.8%. Meanwhile, the service quality and professionalism of BKPSDM employees affected the satisfaction level of unmarried female civil servants by 56.7%. The conclusion of this study showed that the satisfaction level of married women civil servant tends to be lower than the satisfaction level of unmarried women civil servant. Married female civil servants tend to be less patient in the service process. Married women civil servants wanted employees to handle every complaint quickly and as soon as possible. Furthermore, unmarried female civil servants tend to behave in an orderly and obedient manner and more patient in doing management in the service process. They were happy with the disclosure of information obtained from BKPSDM employees so that they had high satisfaction. Keywords: Service quality, Professionalism, Job Satisfaction, Profit Econonomic